Impact of Patient Safety Culture on Job Satisfaction and Intention to Leave Among Healthcare Workers: Evidence from Middle East Context - Al-Surimi K; Almuhayshir A; Ghailan KY; Shaheen NA (Dove Medical Press, 2022)
Khaled Al-Surimi,1- 4 Amirah Almuhayshir,1 Khalid Y Ghailan,5 Naila A Shaheen6- 8 1College of Public Health and Health Informatics, King Saud Bin Abdul-Aziz University for Health Sciences, Riyadh, Saudi Arabia; 2School of Health and Environmental Studies, Hamdan Bin Mohammed Smart University, Dubai, United Arab Emirates; 3Community Medicine and Public Health, Faculty of Medicine and Health Sciences, Thamar University, Dhamar, Yemen; 4King Abdullah International Medical Research Center, Riyadh, Saudi Arabia; 5Faculty of Public Health and Tropical Medicine, Jazan University, Jazan, Saudi Arabia; 6Department of Biostatistics and Bioinformatics, King Abdullah International Medical Research Center, Riyadh, Saudi Arabia; 7King Saud Bin Abdul-Aziz University for Health Sciences, Riyadh, Saudi Arabia; 8Ministry of National Guard-Health Affairs, Riyadh, Saudi ArabiaCorrespondence: Naila A Shaheen, Department of Biostatistics and Bioinformatics, King Abdullah International Medical Research Center, King Saud bin Abdulaziz University for Health Sciences, Ministry of National Guard-Health Affairs, P.O. Box 22490, Mail Code 1515, Riyadh, 11426, Saudi Arabia, Tel +966-11-4294472, Fax +966-11-4294466, Email ashrafna@mngha.med.saBackground: The association between patient safety culture and staff outcomes remains unclear to date. This study aimed to identify the relationship between patient safety culture/job satisfaction and intention to leave among healthcare workers.Methods: A cross-sectional study was conducted using an online survey. Multinomial logistic regression analysis was used to investigate the association between the safety culture dimensions and the outcomes in terms of job satisfaction and intention to leave.Results: Majority were females (77.2%); age between (20- 30) years were (66.1%). 1- 5 years work experience was reported by (98.2%); nurses accounted for (75.7%). (62.1%) reported very good patient safety grade. (78.3%) of respondents had no intention to leave; (84.3%) reported they like their job, (70.5%) stated that working in this hospital is like being part of a large family. However, (38%) said the hospital is not a good place to work, and morale in their clinical area is low. The overall composite scores were highest for "teamwork within hospital units (81.4)", and "organizational learning (79.4)", while lowest for "communication openness (37)",staffing (26.5)", and "non-punitive response to error (22.1)". Females were two times more likely to leave their jobs compared to males (AOR: 2.36, 95% CI: 1.24- 3.46); intention to leave was 3.35 (95% CI = 2.19- 5.09). As for job satisfaction, ages between 31- 40 years tend to like their job two times more than other age groups (AOR: 1.90, 95% CI = 1.02- 3.55). The safety culture domains "staffing" and "hospital management support for patient safety" were linked to a higher odds ratio for job satisfaction.Conclusion: Aside from gender and age, the dimensions of safety culture, including staffing, hospital management support, hospital handover, and transition, may have a signification impact on job satisfaction and intention to leave among healthcare workers.Keywords: patient safety culture, staff outcomes, job satisfaction, intention to leave, healthcare workers